Influence of complex descongestive physical therapy associated with intake of medium-chain triglycerides for treating upper-limb lymphedema - de Oliveira, Jussara; César, T. B. [UNESP] (My University, 2008)
Objective: To investigate the influence of complex decongestive physical therapy (CDP) in association with diet therapy using medium-chain triglycerides (MCT), as an intervention in cases of upper-limb lymphedema. Methods: The lymphedema was evaluated by measuring circumferences, volumes, skin folds and whole-body water content. Feelings of discomfort, pain and heaviness in the arms were evaluated using a visual analog scale. Ten women who had undergone mastectomy and presented upper-limb lymphedema homolateral to the surgery participated in this study. Their mean age was 65.9 ± 10.4 years and their mean body mass index (BMI) was 28.8 ± 3.0kg/m2. After nutritional evaluation, they were randomly divided into two groups: the Control Group (n= 5), which underwent physical therapy treatment consisting of CDP (classical massage, manual lymphatic drainage, compression taping and skincare) three times a week, for four weeks; and the MCT Group (n= 5), which underwent the same physical therapy protocol with the addition of daily diet therapy consisting of intake of MCT, for four weeks. Results: At the end of the intervention, analysis of the circumference and volume measurements showed significant differences between the groups (p≤0.05), with a greater reduction in lymphedema in the MCT Group. There were no significant differences in the skin fold measurements or whole-body water content. The feeling of heaviness in the arms after the intervention was significantly less in the MCT Group (p≤ 0.05), compared with before the intervention. Conclusion: Physical therapy treatment together with diet therapy with intake of MCT in women with upper-limb lymphedema following surgery and breast cancer treatment was effective in reverting this condition.
Keywords: Complex decongestive physical therapy; Diet therapy; Lymphedema; Medium-chain triglycerides